Examining Effective Management and Leadership Strategies in Conflict Resolution: A Case Study of Conflict Management in Private Secondary Schools - Sintapertiwi, Dhian; Ali, Andi Ibrahim; Andika, Mayola (Muslim Education Review, 2023)
This study highlights private schools' management and leadership strategies in dealing with conflicts. School conflicts occur for many reasons. To address the conflicts effectively, schools need to have the ability to thoroughly examine the root cause of such conflicts. The impact on school development in terms of performance largely depends on how school leaders effectively manage and address conflicts. This qualitative research specifically choose private schools due to their autonomy, which distinguishes them from public schools in terms of decision-making and leadership approaches. Data was collected through semi-structured interviews, and analysed using manual thematic analysis methods. This study discovered that conflicts often occur within the scope of appointing new school principals, upholding the integrity of school members, and managing the resistance among teachers. The strategy predominantly used in schools in this study is a win-lose approach, where problems are resolved quickly without considering the need for negotiation. The two schools investigated in this study view future conflicts as a form of competition with other schools, placing strong emphasis on the significance of fair policies for all, and the stakeholders’ trust as the main key.